Manajemen Peningkatan Mutu Akademik SD Negeri Sawojajar 01 Kecamatan Wanasari Kabupaten Brebes - Lestari, Dewi Amelia; Abdullah, Ghufron; Ginting, Rosalina Br. (Jurnal Inovasi Pembelajaran di Sekolah, 2024)
SDN Sawojajar 01 is the best one of SPMI model school at the Central Java provincial in 2018. Apart from that, this school also has good academic quality management. This is proven by the many academic competitions won and good graduation results. The focus of this research is management of improving academic quality at SDN Sawojajar 01, Wanasari District, Brebes Regency. With sub-focus including (1) planning, (2) organizing, (3) mobilizing and (4) monitoring the academic quality of SDN Sawojajar 01. This research aims to describe and analyze academic quality at SDN Sawojajar 01 which includes (1) planning, (2) organizing, (3) actuatting and (4) supervising. The benefits of this research include theoretical and practical benefits. It is hoped that the theoretical benefits can provide scientific contributions for studies and research materials. The practical benefits are for teachers, schools and education services to be taken into consideration in improving academic quality even better. This research uses a qualitative approach with a case study type of research. Data were collected using interviews, observation and documentation methods, while data validation was carried out through triangulation. The results of the research show that quality management in improving the academic quality of SD Negeri Sawojajar 01, Wanasari District, Brebes Regency is carried out in a structured manner starting from planning, organizing, implementing and supervising by involving the active role of teachers, school committees and parents in the functions and responsibilities for improving academic quality. At school, although there are several obstacles faced, they can be resolved well. Academic quality management plays a very important role in improving academic quality at SD Negeri Sawojajar 01. Quality management coordinates 4 elements, namely planning, organizing, implementing and monitoring which are mutually supportive and sustainable and bring about changes in the quality of schools, educational services and the quality of graduates in accordance with community needs. . Based on the research results and conclusions above, recommended by the principal, teachers and school committees can continue to build effective communication and continue to develop knowledge of school management as well as improve discipline and a culture of helping each other to improve the academic quality of SDN Sawojajar 01.